PENGARUH VARIASI JUMLAH LAPISAN FIBERGLASS DAN ANYAMAN BAMBU TERHADAP KEKUATAN BENDING KOMPOSIT DENGAN METODE VACUUM ASSISTED RESIN INFUSSION (VARI) - Achmad Zainuri; Agus Dwi Catur; M. Zazali M. Zazali (Universitas Wahid Hasyim, 2019)
The objective of this research is to obtain the bending properties of composite material produced by VARI method, and to get analysis of polyester resin distribution time on the layer of fiberglass composite and bamboo woven strip.The process of making composites varies, but the process of making this research is the process of Vacuum Assisted Resin Infusion (VARI). In the VARI process, dry fiber is placed between the fixmold and plactic bag, then the resin is injected after the chamber inside the low- pressure plastic bag and the process continues until all parts of the fiber are wetted by the resin.From the results of research, testing and discussion of bending test results that have been done then can be drawn conclusions include: Variation of the number of reinforcement layer on VARI method will affect the value of bending strength of composite. By using the VARI method The highest average value of bending stress occurs in variation 4 (206,69 MPa), while the lowest occurs in variation 1 (42,83 MPa), and the time required for the distribution of resin varies in time variation 1 which takes 5 minutes 02 seconds, while for variation 4 takes 8 minutes 3 seconds.Keywords: composites, VARI method, glass fiber, bending test